The Regulation of Religion and the Making of Hinduism in Colonial Trinidad - Rocklin, Alexander (Book collections on Project MUSE., 2019)
"How can religious freedom be granted to people who do not have a religion? While Indian indentured workers in colonial Trinidad practiced cherished rituals, "Hinduism" was not a widespread category in India at the time. On this Caribbean island, people of South Asian descent and African descent came together--under the watchful eyes of the British rulers--to walk on hot coals for fierce goddesses, summon spirits of the dead, or honor Muslim martyrs, practices that challenged colonial norms for religion and race. Drawing deeply on colonial archives, Alexander Rocklin examines the role of the category of religion in the regulation of the lives of Indian laborers struggling for autonomy"--